Oxford Energy Forum, Issue 101 - Bassam Fattouh; Jonathan Stern; Howard Rogers (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2015)
This issue of the Oxford Energy Forum is dedicated to gas pricing. A mild 2013/14 winter in Europe and parts of Asia and a slowing of demand growth for LNG saw European hub prices and LNG spot prices begin to fall through the summer of 2014. The collapse of the oil price in late 2014 resulted in a lagged reduction in long-term contract prices (LNG and pipeline gas) to levels below 10/MMBtu in Europe and Asia. These events followed a period from 2011 to 2013 in which regional gas reference prices in the USA, Europe, and Asia appeared to be held within stable &8216;corridors' at levels which incentivized the progression of a long list of new LNG projects in North America, East Africa, Australia, and Russia. Many of these will likely be &8216;on hold' pending indications of a more supportive future price environment, but some 150 bcm/year of new LNG supply from the USA and Australia will have achieved start-up by 2020; this will add further pressure on prices and stimulate inter-regional arbitrage.
Keywords: 330